Ancestry background of a population sample from Bolivar Department, Colombia. (December 2015) - Martínez, B.; Builes, J.J.; Aguirre, D.; Mendoza, L.; Afanador, C.H.; Meza, C.; Marrugo, J.
Abstract: The current population of the Bolivar Department is the result of admixture between the European settlers, African slaves and Native Americans. In order to know the ancestry proportions we analysed 46 AIM-InDels in 78 individuals belonging to the north region of this department, according to the methodology described in Pereira et al. [9] . All ancestry estimates were tri-hybrid; 21.5% of the contribution was African, 29.4% was Native American and 49.1% was European. This finding is coherent with recently reports of internal migration patterns. Our findings will be useful to investigate the influence of ethnicity in genetic complex diseases, like asthma and other prevalent conditions.